Peningkatan Relevansi Pelatihan dengan Kesempatan Kerja - Totok Mardikanto (Universitas Negeri Malang, 2016)
The study was designed as a descriptive research involving 75 training managers and facilitators, and 750 graduates in Central Java. Data collection was done by a questionaire and indepth interview. The data were analyzed by descriptive statistics and rank order correlation. The findings of this research indicated that the institutional quality, participant knowledge about job information and job opportunities, participant motivation, graduate quality, and graduate entrepreneurship seemed to be variables having significant correlations with job-opportunity.